A FTIR study of the metal-support interactions and hydrogen spillover on Pd/TiO2 and Ni/TiO2 - Faccin, Flávio; Guedes, Fabiana Flores; Benvenutti, Edilson Valmir; Moro, Celso Camilo (Eclética Química, 2002)
Nickel and palladium dispersed on titania support were submitted to reductive treatment, under hydrogen, at 200 and 500 ºC. After the reductive thermal treatment the materials were exposed to carbon monoxide (10 Torr) and analyzed in the infrared region. The increasing of the electronic density in the metallic d subshell, produced by the reductive thermal treatment, was monitored by the infrared stretching band shift of carbon monoxide adsorbed and it was interpreted as a consequence of the metal-support interactions. The highest effect was observed for Pd/TiO2 system. From the FTIR spectra was also observed that the hydrogen spillover was stronger on Pd/TiO2 than Ni/TiO2 system.